Assessing network security - Lam, Kevin (Microsoft Press, 2004)
Help beat the hackers at their own game! Discover how to take charge of system assets through hands-on vulnerability scanning, penetration testing, and other advanced testing techniques--straight from members of the Microsoft Security Team.
Includes bibliographical references (pages 515-526) and index. - Print version record
Keywords: Computer networks -- Security measures; Réseaux d'ordinateurs; Sécurité; Mesures; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Computer networks; Security measures